Journalism ethics a philosophical approach - Meyers, Christopher (New York ; Oxford : Oxford University Press, 2010)
This title is a reminder, a defense and an elucidation of core journalistic values, with particular emphasis on the interplay of theory, conceptual analysis and practice. Top scholars from philosophy, journalism and communications offer essays on such topics as objectivity, privacy, confidentiality, conflict of interest, and much more.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Journalistic ethics